(untitled) (Quinto Sol, 2020)
This article analyzes the trajectory of the Intransigent Party of Argentina during the period of democratic reconstruction following the last military dictatorship (c.1982-1991), in a microanalytical perspective. Based on the study of this organization in the city of Mar del Plata, the text shows specificities of the local case. At the same time, we examine the characteristics, tensions and conflicts that affected this political force at different scales, in Buenos Aires province and at the national space. In a broad sense, it contributes to the knowledge of the challenges faced by the minority political parties in democracy, the processes of internal fragmentation and the study of the political-party youths in light of a force that was self-represented as national, popular and revolutionary.